Relevansi Akad Ijarah Pada Pembiayaan Umroh di Bank Syariah Kantor Pusat Jakarta Perspektif Hukum Islam - Oktaviani, Feni (Iqtishodia: Jurnal Ekonomi Syariah, 2018)
This research is intended to acknowledge the position of ijarah agreement that used in Umrah bailouts fund specifically Umrah financing at Sharia Mandiri Bank Head Office Jakarta. Additionally, to acknowledge how the implementation of the Umrah financing products when paired with ijarah agreement. The method used is qualitative by means of analytical descriptive methods. This study defined primary and secondary data that obtained from the descriptive research location. Wherewith collecting the primary or secondary data that obtained in the form of interview results of Sharia Mandiri Bank, documentation and also literature study related to this study. The results of this study displayed that this Umrah financing products are right when paired with ijarah agreement. All scholars also allow the validity of this ijarah agreement in muamalah. This ijarah agreement also had the strong foundation of the three basic Islamic law, the Qur?an, the Hadith and Ijma. Furthermore, this results of this also elaborated how the implementation of Umrah financing scheme and did not encounter any problems that may cause ijarah agreement to be void, because of this product is based on Fatwa of National Sharia Council No. 09/DSN-MUI/IV/2000 in respects of ijarah financing, and No. 44/DSN-MUI/VIII/2004 multi-service financing.